The genius bat : the secret life of the only flying mammal - Yovel, Yossi (Ecologist and neurobiologist) (St. Martin's Press, 2025)
"An awe-inspiring tour of bat world by the world's leading expert With nearly 1500 species, bats account for more than twenty percent of mammalian species. The most successful and most diverse group of mammals, bats come in different sizes, shapes, and colors, from the tiny bumblebee bat to the giant golden-crowned flying fox. Some bats eat fruit and nectar; others eat frogs, scorpions or fish. Vampire bats feed on blood. Bats are the only mammals that can fly; their fingers have elongated through evolution to become wings with a unique super-flexible skin membrane stretched between them. Their robust immune system is one of the reasons for their extreme longevity. A tiny bat can live for forty years. Yossi Yovel, an ecologist and a neurobiologist, is passionate about deciphering the secrets of bats, including using AI to decipher their communication. In The Genius Bat he brings to vivid life these amazing creatures as well as the obsessive and sometime eccentric people who study them-bat scientists. From muddy rainforests, to star-covered night deserts, from guest houses in Thailand, to museum drawers full of fossils in New York, this is an eye-opening and entertaining account of a might mammal."-- Provided by publisher.